2001
DOI: 10.1021/jm000417f
|View full text |Cite
|
Sign up to set email alerts
|

Structure−Activity Relationships at Monoamine Transporters and Muscarinic Receptors for N-Substituted-3α-(3‘-chloro-, 4‘-chloro-, and 4‘,4‘ ‘-dichloro-substituted-diphenyl)methoxytropanes

Abstract: The design, synthesis, and evaluation of 3alpha-(diphenylmethoxy)tropane (benztropine) analogues have provided potent and selective probes for the dopamine transporter. Structure-activity relationships (SARs) have been developed that contrast with those described for cocaine, despite significant structural similarity. Furthermore, behavioral evaluation of many of the benztropine analogues in animal models of cocaine abuse has suggested that these two classes of tropane-based dopamine uptake inhibitors have dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 20 publications
0
33
1
Order By: Relevance
“…When the diphenyl ether substituents increased in steric bulk (e.g. 4′,4″-di Cl) N-substitution resulted in further decreases in DAT affinity [78]. However, a notable separation of DAT from muscarinic M1 receptor binding was achieved, with several analogues in this series having > 100-fold selectivity for DAT [77,79,80].…”
Section: Sar Studies With Benztropine Analogsmentioning
confidence: 94%
“…When the diphenyl ether substituents increased in steric bulk (e.g. 4′,4″-di Cl) N-substitution resulted in further decreases in DAT affinity [78]. However, a notable separation of DAT from muscarinic M1 receptor binding was achieved, with several analogues in this series having > 100-fold selectivity for DAT [77,79,80].…”
Section: Sar Studies With Benztropine Analogsmentioning
confidence: 94%
“…37 An extension of this investigation into optimal N-substitution with varying substitutions on the diphenyl ether have also recently been described. 38 The 3D-QSAR models have been further refined by inclusion of additional structural data ( Fig. 1) These modeling studies showed that for the benztropine series of compounds, the steric interactions along with the electrostatic contributions guided the binding affinity to the DAT.…”
Section: Structure-activity Relationships At Datmentioning
confidence: 99%
“…In the benztropine series, replacement of the N-methyl group of several halogenated aryl-ring substituted compounds with a propylphenyl group served to decrease binding affinity slightly (K i ¼ 40-160 nM). 32,38 Whereas, in the 4 0 ,4 00 -diF-BZT series, optimal DAT binding affinity was achieved with the N-4 00 -phenyl-n-butyl substituent (43). 32 The Nbenzyl analog was less active (64; K i ¼ 82 nM).…”
Section: Gbr 12909 and Its Analoguesmentioning
confidence: 99%
“…[12][13][14][15] Furthermore, the SAR of analogs bearing different substituents on the N-8 nitrogen have been explored. [16][17][18][19] In continuation of the efforts to explore the SAR of BZT analogs, this report examines the isosteric replacement of the benzhydrol ether moiety by a benzhydryl amino group. If such a modification is tolerated at the DAT, it is expected that, compared to their corresponding BZT analogs, the resulting benztropinamine derivatives 4a-m might be more chemically stable and the water solubility might be improved.…”
mentioning
confidence: 99%
“…As with 4a, the M1 over DAT selectivity was reduced compared to the corresponding ether derivatives. Only the derivative 4d, with a 3,4-dichloro substitution on both phenyl rings, 18 Binding data were analyzed as described in Table 1. has a somewhat higher binding affinity at the DAT (2-fold) and a higher DAT over M1 selectivity than 4a. However, with 4d DAT selectivity over NET was reduced by 3-fold.…”
mentioning
confidence: 99%